Teori Anxiety dalam Preferensi Pemilihan Sekolah dalam Pandangan Psikologi Islam - Qoirunnisa, Fentika Zahra; Qodriyah, Laelatul; Az-Zahra, Namira; Kunaepi, Aang (Pascasarjana IAIN Metro, 2024)
Education is an important thing for humans. The human need for education is primary. However, in pursuing education, schools are needed which are the category of formal education. School is a way to get an education. However, over time, school selection has become a scourge for children. The underlying factors are the zoning registration system, and the dominance of parents in determining schools. Parents tend to refer to madrasas or Islamic-based schools in the hope of getting more integrated Islamic lessons. This gives rise to a feeling of anxiety in children and are not free in determining their choices. This article will discuss the causes of the appearance of symptoms anxiety in children in school selection preference. This case study took place on Jl. Margosari rt.04 rw.07, Sawah Besar, Gayamsari, Semarang. This research uses the case study method and literature study at the same time. The results revealed that 25% of children objected if their parents forced them to attend further education at madrasah.